2016
DOI: 10.3389/fpsyg.2016.00982
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Self-Esteem and Perceived Parent–Child Relationship in Early Adolescence

Abstract: Aims: Early adolescence represents a critical developmental period both from a psychological and a psychopathological point of view. During this period, one of the most common disorders that frequently arise is represented by depression, that tends to become chronic and may produce many subsequent psychosocial impairments. The present study aimed to analyze characteristics of depressive symptoms in an Italian sample of early adolescents, and to explore their connections with self-esteem levels and perceived ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 46 publications
(56 reference statements)
5
56
0
8
Order By: Relevance
“…It also has been shown that parental concordance for psychopathology is related to greater psychopathology in children (Merikangas, Prusoff, & Weissman, ). These findings have highlighted the importance of examining mental health in both parents in studying the links between parental psychopathology and offspring outcomes (Babore, Trumello, Candelori, Paciello, & Cerniglia, ; Connell & Goodman, ). It was demonstrated that children of ED parents are at higher risk for the onset of psychopathologies, but the underpinning mechanism that is responsible for mediating factors that foster or impede the development of psychiatric symptoms in offspring is not yet clear, and previous studies have found mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that parental concordance for psychopathology is related to greater psychopathology in children (Merikangas, Prusoff, & Weissman, ). These findings have highlighted the importance of examining mental health in both parents in studying the links between parental psychopathology and offspring outcomes (Babore, Trumello, Candelori, Paciello, & Cerniglia, ; Connell & Goodman, ). It was demonstrated that children of ED parents are at higher risk for the onset of psychopathologies, but the underpinning mechanism that is responsible for mediating factors that foster or impede the development of psychiatric symptoms in offspring is not yet clear, and previous studies have found mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…The environment in which the early adolescents are raised and their relationship with their parents largely contribute to their psychological well-being (Bulanda & Majumdar, 2009;Stafford, Kuh, Gale, Mishra, & Richards, 2016). Emerging evidence has shown that self-esteem of the adolescents can be determined within the context of the parent-child relationship (Babore, Trumello, Candelori, Paciello, & Cerniglia, 2016;Bulanda & Majumdar, 2009). Over the past few decades, developmental psychologists have been interested in the role of parents in children's development, and one of the study areas that has been extensively explored is parenting style (Darling & Steinberg, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In adolescence, perception of closeness with parents positively correlates with self‐esteem (Babore, Trumello, Candelori, Paciello, & Cerniglia, ; Parker & Benson, ). Bulanda and Majumdar () considered family as an important arena that influences children's perceptions of their self‐worth.…”
Section: Introductionmentioning
confidence: 99%